SYNTHESIS AND CRYSTAL STRUCTURE OF A CU(II) COMPLEX AND ITS CATALYTIC ACTIVITY FOR THE OXIDATION OF BENZYL ALCOHOL - JIE YIN; XI-SHI TAI; QIAN-QIN GUO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
A Cu(II) complex, [CuL2(Phen)] (1) (HL = 2-benzoylbenzoic acid, Phen = 1,10-phenanthroline), has been synthesized and structurally characterized by elemental analysis and single-crystal X-ray diffraction. Structural analysis indicated that the Cu(II) complex (1) belongs to the monoclinic system with P21/c space group, and a = 18.955(4) Å, b = 8.3618(17) Å, c = 27.890(8) Å, β = 131.635(18)°, V = 3303.8(15) Å3, Dc = 1.396 g·cm-3, the final R = 0.0505, wR2 = 0.1154 with I≥2σ (I). In Cu(II) complex, both the COO- group of L ligand and Phen ligand adopt bidentate coordination mode. The Cu(II) center is six-coordinated by two N atoms of one Phen ligand and four O atoms of two different L ligands, forming a distorted octahedral coordination environment. The Cu(II) complex (1) molecules forms a 1D chain structure by π-π stacking effect of neighboring benzene rings, and the 1D chains further form a 3D network structure. The catalytic activity of [CuL2(Phen)] (1) for the oxidation of benzyl alcohol has been tested with O2 as the oxidant.